Measurement of differential cross sections of elastic scattering of protons by nuclei 14N at Ep, lab. = 0.7 – 1.1 MeV - Буртебaев, Н.; Керимкулов, Ж.К.; Юшков, А.В.; Зaзулин, Д.М.; Aлимов, Д.К.; Джaнсейтов, Д.М.; Мухaмеджaнов, Е.С.; Нaсурллa, М.; Шaкиров, А.К.; Пaттaев, А. (Recent Contributions to Physics, 2018)
The differential cross sections of elastic 14N(p,p)14N scattering at energies of protons 0.7 – 1.1 MeV and scattering angles θc.m. = 320-1660 have been measured. The analysis of data in this work and the available literature data on elastic scattering of protons on 14N nuclei in the optical model were obtained. The optimal value of the optical potential parameters that will be needed in the calculation of the processes occurring in hybrid nuclear reactors and thermonuclear installations. Theoretical analysis was carried out using a FRESCO settlement program. Parameters of the potential corresponding to optimally match of the experimental and calculated values of the differential cross sections, were found minimizing the value of χ2.
Keywords: elastic scattering, Faraday cup, Fresco, differential cross sections